(untitled) (Vietnam Journal of Community Medicine, 2024)
Introduction: Penile cancer is a rare disease but has a significant impact on quality of life. It has been found that early inguinal lymphadenectomy can reduce the recurrence rate and provide long-term survival advantages to patients. Endoscopic inguinal lymph node dissection technique is proposed to reduce complications of open surgery. Objective: To research and report initial results on the effectiveness of laparoscopic inguinal lymphadenectomy in treatment penile cancer at the Andrology department- 108 Central Military Hospital. Series case report: There were 03 cases of penile cancer that underwent endoscopic inguinal lymphadenectomy from October 2023 to March 2024. Average dredging time per groin was 110.83 minutes. The average number of lymph nodes on both sides was equivalent, at 8.83 lympho nodes per groin, with no metastatic ones. No patient had complications such as surgical wound infection, skin necrosis, postoperative lymphatic cysts, venous thrombosis or pulmonary artery thrombosis. 02 patients had mild edema of both lower extremities when walking a lot or standing for long time, and they had disappearred by conservative treatment. The patients were satisfied with the surgical results. Discussion: To discuss the general characteristics of patients and the technical characteristics of endoscopic inguinal lymphadenectomy to treat penile cancer; as well as emphasizing the effectiveness and safety of the technique. Conclusion: Initial results show that endoscopic inguinal lymphadenectomy surgery in the treatment of penile cancer being performed at Central Military Hospital 108 is feasible, safe, effective, and it limits the rate at complications compared to the technique of open lymph node dissection.